The Role of Village Fund Allocation (ADD) in Improving Community Welfare Through Village Potential - Eva Herianti; Litdia Litdia (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
Corruption in village fund allocation involving village officials has become a grave concern for the government. This condition will undoubtedly reduce the community's welfare, given that village fund allocation is used to satisfy personal gains instead of fulfilling the primary needs of the community. Therefore, this study aims to examine and analyze the effect of village fund allocation on community welfare through village potential. The sample of this study comprises provincial governments using the purposive sampling method, which reports village financial data from 2017 to 2019. The panel data regression method was used in this study to test the hypothesis with the help of Eviews version 11. This study revealed that the allocation of village funds had a positive and significant effect on community welfare. However, village potential cannot strengthen the influence of village fund allocation on community welfare. This study also discovered that the level of community welfare was high due to the village revenue effectiveness. However, no significant difference was found under the category of village spending efficiency on community welfare. In other words, village fund allocation that is spent optimally by the village government for its various strategic programs will positively impact community welfare. This study aims to address the gap found in previous literature by formulating the measurement of the variable allocation of village funds and village potential, which is still limited by using secondary data.